Confirmatory Detection of Escherichia Coli O157:H7 in Diarrheic and Non-Diarrheic Calves by using Real Time PCR with Studying the Antimicrobial Susceptibility of these Bacteria - Mustafa Salah Hasan (Journal of Global Pharma Technology, 2018)
Shiga toxigenic E. coliO157:H7 is one of the Shiga-toxin producing types of E. coli, which can produce disease in man and animals. The aims of this study were to detect O gene (rfbO157) and H gene (fliCH7) and determine the pattern of antimicrobial susceptibility of 32 E. coli O157:H7 isolates. The isolates isolated by conventional culture methods and latex test from faecal samples of 4 calves suffering from diarrhoea and 28 calves’ apparent normal. DNA was extracted from these isolates and the real time PCR was applied on the extract of DNA for confirming the diagnosis ofrfbO157 and flic H7 genes. Seven antimicrobial discs were used in this study. The result presented that all the (32) isolates were possessed the rfbO157 and flics H7 genes. The susceptibility test of the isolates revealed that all isolates were highly resistant to Erythromycin (100%) and Cephalothin (96.87 %). Less resistance to Tetracycline, Trimethoprim-Sulfamethoxazole and Chloramphenicol at different percentage (31.25%), (12.5%) and (9.37%) respectively and all isolates showed high sensitivity to Gentamicin (100 %), Enrofloxacin (100 %). In conclusion, the real time PCR can be used as a sensitive and reliable tool for diagnosis of E. coli O157:H7 and these bacteria showed high resistance to antibiotic.Keywords: E. coli O157:H7, real time PCR, rfbO157, flic H7, antibiotic susceptibility.